Retention and Expansion of Foreign Direct Investment : Political Risk and Policy Responses - World Bank (World Bank, Washington, DC, 2019)
Due to its recognized benefits, most countries today regardless of their level of development compete for and dedicate significant resources to attracting foreign direct investment (FDI). Capturing the full positive spillovers of FDI is a long-term process and requires regulatory certainty and predictability to enable strategic business planning. This paper aims to fill this gap in evidence-based policy making, by contributing to the understanding of how political risks emanating from government conduct affect FDI and proposing a tool for governments to help investors retain and expand investments. Based on investor survey data and empirical analysis of investor-state dispute settlement (ISDS), the paper aims to draw attention to this issue and to highlight that many countries may inadvertently be losing significant amounts of FDI. The paper responds to an urgent need for governments to provide a minimum institutional infrastructure that can enable a lead agency to identify, track, and manage conflicts arising between investors and public agencies as early as possible.